Employing Artificial Intelligence Applications in TV News Production: A Case Study on Saudi News Channel (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to identify the most important aspects of artificial intelligence techniques in the field of television news production, monitor the mechanisms for their development, and evaluate the processes of television news production using artificial intelligence. And to reveal the obstacles and challenges facing television news production.The media survey method will be used through a survey study applied to Al-Ikhbariya channel. One of the most prominent expected results of this study is the impact of artificial intelligence applications on the process of television news production from collecting, editing, directing and presenting television news.The study belongs to descriptive studies, and relies on the survey method. The questionnaire tool was used as a tool for collecting data, by applying it to a sample of employees of the Saudi Al-Ikhbariya channel consisting of (65) individuals.The study reached a set of results, the most prominent of which are: The study sample respondents believe that (artificial intelligence applications supporting news gathering) came at the forefront of artificial intelligence applications used in producing television news, with a percentage of (38.9%). In second place came (artificial intelligence applications for editing news), with a percentage of (36.1%), while (artificial intelligence applications used in filming news) came in third and last place with a percentage of (25%). The respondents believe that the skill (programming) comes at the forefront of the skills that news workers must learn to keep pace with the development of artificial intelligence technologies, with a percentage of(53.8%) ., In second place came the skill (data analysis) with a percentage of (50.8%), followed by the skill (interaction with robots) in third and last place with a percentage of (35.4%).The proposal (developing the skills of workers in television news production) came at the forefront of the respondents’ proposals in order to achieve a balance in the use of artificial intelligence and the role of the human element. In second place came the proposal (imposing restrictions on the use of artificial intelligence applications), followed by the proposal (using specific applications of intelligence applications in news production) in third place.
Keywords: Artificial Intelligence Applications; Production; Television News; Saudi News Channel